Human sexuality and the family - Maddock, James W (Haworth Press, 1983)
"Has also been published as Marriage & family review, volume 6, number 3/4, fall/winter 1983"--T.p. verso.; Includes bibliographies; Neal A. Newfield, Ph.D., LICSW (Giver)